Multiple sclerosis: long‐term outcomes in ethnic minorities. Analysis of a UK population‐based registry. (16th February 2018) - Alsaeed, M. O.; Harding, K. E.; Williams, O. H.; Willis, M. D.; Hrastelj, J.; Tallantyre, E. C.; Joseph, F. G.; Wardle, M.; Pickersgill, T. P.; Robertson, N. P.
Abstract : Background and purpose: Multiple sclerosis (MS) is most frequent in Caucasian populations. However, studies of MS in other ethnic groups may offer unique insights into genetic and environmental influences on the disease, and data on long‐term outcomes in these patients is limited. In this work clinical features and time to disability milestones were investigated in ethnic minority (EM) patients with MS in a UK population and comparisons were made to a Caucasian cohort from the same region. Methods: In all, 1949 MS patients (1866 Caucasian, 83 EM) were identified from a regional disease registry. Cox proportional hazards regression was used to analyse the time to Expanded Disability Status Scale (EDSS) 3.0, 4.0 and 6.0. Results: Ethnic minority patients were younger at disease onset (28.6 years vs. 32.8 years, P  = 0.001), and primary progressive MS was less common (EM 4.8%, Caucasian 11.6%, P  = 0.03). After correction for clinical variables, ethnicity was associated with time to EDSS 3.0 [EM: hazard ratio (HR) 1.75, P  < 0.0001] and 4.0 (HR 1.46, P  = 0.03), but not 6.0 (HR 1.5, P  = 0.05). Conclusions: Ethnic minority patients reach early levels of fixed disability more rapidly than Caucasian patients, but this effect diminishes at later stages of the disease. This has implications for clinical management of these patients. Abstract : Clickhere to view the accompanying paper in this volume.